Topcoat layer, laminated film containing same, and decorative article decorated by said laminated film

By coating materials composed of acrylic polymers and polytyck acid esters, the facial paint layer with high total extension and pencil hardness is formed, which solves the tension problem caused by the deformation of the existing technology. Excellent performance and durability.

CN119384442APending Publication Date: 2025-01-28BASF COATINGS GMBH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380046321.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-16
Filing Date
2023-05-22
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the prior art, the topcoat layer used for three-dimensional molding decoration has a major problem of deformation and causing tension, which may cause the topcoat layer to break and affect the appearance and tolerance of the decorative products.

Method used

Adopt coating materials composed of acrylic polymers, polychide, and solvents. The top paint layer is formed by applying coating to ensure that the surface paint layer has 3 % or larger total extension rates and larger total extension rates and a larger total extension rate and a larger total extension rate and a larger total extension rate and a larger extension rate. 6B or higher pencil hardness.

Benefits of technology

The excellent appearance, modularity, chemical resistance, water resistance and weather resistance of the facial paint layer are realized to ensure the high quality and durability of decorative products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384442A_ABST
    Figure CN119384442A_ABST
Patent Text Reader

Abstract

Provided are a topcoat layer having excellent appearance, moldability, chemical resistance, water resistance, and weather resistance, a laminated film containing the topcoat layer, and a decorative article decorated with the laminated film. Solution: A topcoat layer (A) having a total elongation and pencil hardness in a specific range in a temperature range of 20 DEG C to 120 DEG C, which topcoat layer is formed by applying a coating layer of a coating material (D) comprising the following base components: an acrylic polymer (B), the acrylic polymer contains a hydroxyl group and has a glass transition temperature in a specific range, a polyisocyanate (C), and a solvent; a laminated film (H) in which the topcoat layer is laminated on a base material; and a decorative article (I) decorated with the laminate film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a topcoat layer, a laminated film containing the topcoat layer and a decorative article decorated by the laminated film. Background Art

[0002] In recent years, from the viewpoints of VOC (volatile organic compound) control, processability and providing functionality, alternative technologies for advanced design coatings have gained attention. Typical examples of decorative technologies that replace conventional methods include applying decorative films to automobile exteriors and parts, colored plastic molded products by using molded-in color, etc., and practical applications have partially begun.

[0003] There are alternative coating technology methods for obtaining plastic decorative articles from decorative films comprising a base material and one or more decorative layers. Generally, injection molding machines are used with these methods.

[0004] Specifically, the film-containing base material and the decorative layer are pre-arranged in the mold. Subsequently, an injection molding machine is used to pour molten resin into the mold to obtain a molded product. The method of leaving both base material and decorative layer in a decorative product like this is called in-mold forming (IMF). On the other hand, by arranging the film in the mold in the same manner as above, but separating the base material from the decorative layer and then pouring molten resin into the mold to leave only the decorative layer in the decorative product is called in-mold release (IMR). In addition, there is also TOM (three-dimensional superposition) molding, which is not limited to plastics, wherein the film is superimposed on the previously completed product by vacuum forming.

[0005] When a decorative part including a decorative film including a base material and one or more decorative layers is obtained by in-mold molding, the topcoat layer, which is the outer layer of the decorative layer and the outermost layer on the decorative article, needs to have moldability to be deformed to match the surface profile of the film. Since large tension is generated in multiple parts of the topcoat layer when the base material is deformed, there is a concern that cracks or the like may be generated in the topcoat layer due to the tension, which may affect the appearance or resistance characteristics (chemical resistance, weather resistance) of the decorative article.

[0006] As an example of conventional technology for decorative films, Patent Document 1 discloses a laminated film for three-dimensional molded decoration, which has a base material film layer, a clear coating layer and a design layer, and the clear coating layer is a layer formed of an active energy ray-curable coating composition.

[0007] Patent Document 2 discloses a conductive composition comprising a formed film having a decorative layer and a conductive layer on a base film, and a polyrotaxane compound for the formed film.

[0008] Patent Document 3 discloses a decorative film for decorating a three-dimensional molded product, wherein the decorative film comprises at least a base material film layer and a transparent layer, and the transparent layer contains a fluorine-containing polymer.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: JP 2021-20412

[0012] Patent Document 2: JP 2021-17507

[0013] Patent Document 3: WO2018-216741 Summary of the invention

[0014] Problems to be solved by the present invention

[0015] However, in Patent Document 1, since an active energy ray-curable coating composition is used in the clear coating film layer, an active energy ray irradiation device is required, and the functional groups remaining after the reaction may affect the molded product. In Patent Document 2, polyrotaxane is a necklace-like sliding ring polymer composed of a linear polyethylene glycol and a plurality of cyclic cyclodextrin molecules, however, due to the hydrophilic nature of polyethylene glycol, the film containing polyrotaxane has the potential to greatly reduce water resistance. In addition, the fluorine-containing polymer of the raw material in Patent Document 3 is expensive, and it is difficult to apply it to automotive parts, especially from the perspective of cost.

[0016] In view of the above conventional techniques, an object of the present invention is to provide a topcoat layer having excellent appearance, moldability, chemical resistance, water resistance and weather resistance, a laminated film containing the topcoat layer, and a decorative part decorated by the laminated film.

[0017] Means used to solve problems

[0018] As a result of diligent research to solve the above-mentioned problems, the inventors have found solutions to the above-mentioned problems and completed the present invention by the following items: a topcoat layer (A) having a total elongation and pencil hardness within a specific range in a temperature range of 20°C to 120°C, the topcoat layer being formed by applying a coating of a coating material (D) comprising the following basic components: an acrylic polymer (B) containing a hydroxyl group and having a glass transition temperature within a specific range, a polyisocyanate (C), and a solvent; a laminated film (H) in which the above-mentioned topcoat layer is laminated on a base material; and a decorative article (I) decorated by the above-mentioned laminated film.

[0019] Specifically, the above-mentioned problems of the present invention are solved by the following items:

[0020] <1> A topcoat layer (A), specifically a floor paint layer (A), that meets the following conditions (1) to (3):

[0021] is formed by applying a coating of a coating material (D) comprising the following essential components: an acrylic polymer (B) comprising a hydroxyl group and having a glass transition temperature of -50°C to 30°C, a polyisocyanate (C), and a solvent;

[0022] having a total elongation of 3% or more within a temperature range of 20°C to 120°C; and

[0023] Having a pencil hardness of 6B or higher as measured in accordance with ISO 15184.

[0024] <2> The hydroxyl value of the above acrylic polymer (B) is preferably 80 to 220 mg KOH / g.

[0025] <3> The polyisocyanate (C) is preferably an aliphatic polyisocyanate.

[0026] <4> The above-mentioned polyisocyanate (C) is preferably one or more substances selected from the group consisting of biuret, isocyanurate, adduct, uretdione and allophanate of a compound having two or more isocyanate groups in the molecule.

[0027] <5> The coating material (D) mentioned above preferably comprises one or more substances selected from polyurethane elastomers (E) or polyesters (F).

[0028] <6> The content ratio of the isocyanate groups in the above polyisocyanate (C) to the hydroxyl groups in the above acrylic polymer (B) expressed as a NCO / OH molar ratio is preferably 0.5 to 1.7.

[0029] <7> The above-mentioned coating material (D) preferably contains a hindered amine-based light stabilizer (G).

[0030] Furthermore, the above-mentioned problems of the present invention are solved by the following items:

[0031] <8> A laminated film (H) formed by laminating the above-mentioned topcoat layer (A) onto a base material.

[0032] <9> The laminated film (H) of the present invention may have a printed layer between the aforementioned base material and the aforementioned topcoat layer (A).

[0033] <10> The laminated film (H) of the present invention preferably has a total elongation of 5% or more in the temperature range of 60°C to 120°C.

[0034] <11> The above-mentioned base material is preferably polypropylene.

[0035] <12> The laminated film (H) of the present invention can be formed by additionally laminating a release layer on the above-mentioned topcoat layer (A).

[0036] Furthermore, the above-mentioned problems of the present invention are solved by the following items:

[0037] <13> A decorative article (I) decorated with the above laminated film (H).

[0038] Effects of the Invention

[0039] According to the present invention, a topcoat layer having excellent appearance, moldability, chemical resistance, water resistance and weather resistance, a laminated film including the topcoat layer, and a decorative article decorated by the laminated film can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 Figure 1 This is a cross section of an example (Example 1) showing the laminated film (H) of the present invention.

[0041] Figure 2 Figure 2 This is a cross section showing one example (Example 2) of the laminated film (H) of the present invention.

[0042] Figure 3 Figure 3 This is a cross section showing one example (Example 3) of the laminated film (H) of the present invention.

[0043] Figure 4 Figure 4 This is a cross section showing one example (Example 4) of the laminated film (H) of the present invention.

[0044] Figure 5 Figure 5 This is a cross section showing one example (Example 5) of the laminated film (H) of the present invention. DETAILED DESCRIPTION

[0045] [Topcoat layer (A)]

[0046] The topcoat layer (A) of the present invention refers to one layer of a laminated film comprising a plurality of layers for applying decoration to an article, and this layer is the outermost layer on the article which has been decorated with this film.

[0047] By satisfying the following conditions (1) to (3), the topcoat layer (A) will have good moldability, and further, the decorative article (I) decorated with the laminated film (H) in which the topcoat layer (A) is laminated onto the surface of any base material will have excellent appearance, chemical resistance, water resistance and weather resistance.

[0048] [Conditions (1) to (3)]:

[0049] (1) is formed by applying a coating of a coating material (D) comprising the following essential components: an acrylic polymer (B) containing a hydroxyl group and having a glass transition temperature of -50°C to 30°C, a polyisocyanate (C), and a solvent.

[0050] (2) Having a total elongation of 3% or more in the temperature range of 20°C to 120°C.

[0051] (3) Having a pencil hardness of 6B or higher measured according to ISO 15184.

[0052] [Total elongation of topcoat layer (A)]

[0053] In the present invention, "3% or more total elongation in the temperature range of 20°C to 120°C" of the topcoat layer (A) indicates a total elongation of 3% or more at any temperature in the temperature range of 20°C to 120°C and means that sufficient stretchability is obtained when the layer is formed at this temperature. By having a total elongation of 3% or more in the temperature range of 20°C to 120°C, breakage will not occur in the topcoat layer (A) when it is stretched, and good appearance of the molded article is maintained.

[0054] The desired total elongation range of the topcoat material (A) can be achieved by adjusting the glass transition temperature or hydroxyl value of the acrylic polymer (B), or the NCO / OH molar ratio which is the mixing ratio of the acrylic polymer (B) to the polyisocyanate (C).

[0055] In order to measure the total elongation, a linerless film of the topcoat layer (A) having dimensions of initial length (L0) = 30 mm, width = 10 mm, and film thickness 30 μm was prepared, and the measurement was performed using Autoclave AG-IS (trade name) manufactured by Shimadzu Corporation at a tensile speed of 5 mm / min in a temperature range of 20° C. to 120° C. The length (L) at the rupture point of the topcoat layer (A) was measured, and the total elongation was determined by the following formula.

[0056] Total elongation (%) = (L-L0) / L0 x 100

[0057] [Pencil hardness of topcoat layer (A)]

[0058] The topcoat layer (A) in the present invention has a pencil hardness of 6B or higher as measured according to ISO 15184. Thus, the topcoat layer (A) obtains sufficient hardness and improved chemical resistance. A topcoat layer (A) pencil hardness of 4B or higher is particularly preferred.

[0059] The desired pencil hardness range of the topcoat layer (A) can be achieved by adjusting the glass transition temperature, mass average molecular weight (Mw) or hydroxyl value of the acrylic polymer (B), or the NCO / OH molar ratio (which is the mixing ratio of the acrylic polymer (B) to the polyisocyanate (C)).

[0060] [Coating material (D)]

[0061] The coating material (D) of the present invention comprises an acrylic polymer (B) which contains a hydroxyl group and has a glass transition temperature of -50°C to 30°C, a polyisocyanate (C), and a solvent as essential components.

[0062] Due to the fact that the coating material (D) contains an acrylic polymer (B) (which contains a hydroxyl group and has a glass transition temperature of -50°C to 30°C) and a polyisocyanate (C), both the total elongation and pencil hardness of the topcoat layer (A) can be achieved, and the appearance, formability, chemical resistance, water resistance and weather resistance can be satisfactory at the same time. Crosslinking through the bonding of the hydroxyl group of the acrylic polymer (B) with the polyisocyanate (C) can further increase the chemical resistance, water resistance and weather resistance. In addition, the density of the coating material (D) and the wettability to the substrate material can be appropriately controlled by including a solvent.

[0063] [Viscosity of coating material (D)]

[0064] In the present invention, although the viscosity of the coating material (D) may depend on the method for forming a coating film, it is preferred to adjust the viscosity to 50 mPa·s to 5000 mPa·s with a solvent at 23°C, and more preferably to adjust the viscosity to 300 mPa·s to 3000 mPa·s. By making the viscosity 50 mPa·s or higher, sufficient film thickness can be ensured, and workability is considered to be satisfactory. By making the viscosity 5000 mPa·s or lower, a coating film is formed in which no air remains in the topcoat layer (A) and no bubbling or the like occurs during molding.

[0065] [Acrylic polymer (B)]

[0066] The glass transition temperature of the acrylic polymer (B) is preferably -50°C to 30°C, more preferably 45°C to 25°C and still more preferably -40°C to 20°C. By making the glass transition temperature -50°C or higher, chemical resistance of the topcoat layer (A) is ensured by sufficient pencil hardness, and by making the transition temperature 30°C or lower, the topcoat layer (A) can obtain total elongation within the target range and good moldability.

[0067] Here, the glass transition temperature is a value calculated from the formula presented below.

[0068] 1 / Tg=Σ(W i / Tg i )

[0069] Tg: glass transition temperature of copolymer (absolute temperature)

[0070] W i : Mass fraction of monomer component i

[0071] Tg i : Glass transition temperature of the homopolymer of monomer component i (absolute temperature)

[0072] [Monomers constituting acrylic polymer (B)]

[0073] In the present invention, the acrylic polymer (B) may be prepared as a copolymer of a hydroxyl group-containing monomer (a) and another monomer (c), preferably a copolymer of a hydroxyl group-containing monomer (a), a carboxyl group-containing monomer (b) and another monomer (c).

[0074] [Hydroxyl-containing monomer (a)]

[0075] A monomer containing a hydroxyl group and a radically polymerizable unsaturated bond can be used as the hydroxyl group-containing monomer (a). The hydroxyl group serves as a functional group that reacts mainly with the polyisocyanate (C).

[0076] The hydroxyl-containing monomer (a) includes 2-hydroxyethyl acrylate (HEA), 2-hydroxyethyl methacrylate (HEMA), 2-hydroxypropyl acrylate (HPA), 2-hydroxypropyl methacrylate (HPMA), 4-hydroxybutyl acrylate (4-HBA), glyceryl monomethacrylate (Blemmer GLM and Blemmer GLM-R (trade names) (chlorine-free type) manufactured by NOF Corporation), etc.

[0077] These hydroxyl group-containing monomers (a) may be used alone, or two or more kinds may be used.

[0078] [Carboxyl group-containing monomer (b)]

[0079] A monomer containing a carboxyl group and a radically polymerizable unsaturated bond can be used as the carboxyl group-containing monomer (b). The carboxyl group-containing monomer (b) includes acrylic acid ester, methacrylic acid ester, 2-(methacryloyloxy)ethyl succinate, and the like.

[0080] These carboxyl group-containing monomers (b) may be used alone, or two or more kinds may be used.

[0081] [Other monomers (c)]

[0082] The other monomer (c) is not particularly limited, provided that it is a monomer containing an unsaturated bond that can be polymerized by free radicals, and it is appropriately selected based on compatibility with other components in the coating material (D). It is preferred to use a monomer having good copolymerizability with the hydroxyl group-containing monomer (a) and the carboxyl group-containing monomer (b) for the other monomer (c).

[0083] Specific examples of other monomers (c) are listed in (1) to (8) below.

[0084] (1) Monoester monomers of acrylic acid or methacrylic acid and 1 to 20C monohydric alcohols: Examples include methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, butyl acrylate, butyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, cyclohexyl acrylate, cyclohexyl methacrylate, lauryl acrylate, lauryl methacrylate, and the like.

[0085] (2) Aromatic vinyl monomers: Examples include styrene, α-methylstyrene, vinyltoluene and the like.

[0086] (3) Glycidyl group-containing vinyl monomer: a compound containing a glycidyl group and a radically polymerizable unsaturated bond in a single molecule, specifically, glycidyl acrylate, glycidyl methacrylate, and the like.

[0087] (4) Nitrogen-containing alkyl (1 to 20C alkyl) (meth)acrylates: Examples include dimethylaminoethyl acrylate, dimethylaminoethyl methacrylate, and the like.

[0088] (5) Amide-based monomers containing a radically polymerizable unsaturated bond: Examples include acrylamide, methacrylamide, N,N-dimethylacrylamide, N,N-dimethylmethacrylamide, N-butoxymethylacrylamide, N-hydroxymethylacrylamide, N-hydroxymethylmethacrylamide, diacetone acrylamide, and the like.

[0089] (6) Aliphatic vinyl compounds: Examples include vinyl acetate, vinyl propionate, vinyl chloride, and the like.

[0090] (7) Nitrile-based compounds containing a radically polymerizable unsaturated bond: Examples include acrylonitrile, methacrylonitrile and the like.

[0091] (8) Diene-based compounds: Examples include butadiene, isoprene, and the like.

[0092] The other monomer (c) may be used alone, or two or more kinds may be used.

[0093] [Production of acrylic polymer (B)]

[0094] In the present invention, the production method for the acrylic polymer (B) is not particularly limited, and for example, the polymer can be obtained by polymerizing the above-mentioned polymer by a known free radical polymerization reaction. Although it is not a problem that the reaction is carried out in the absence of a solvent, it is preferred to use a solvent from the viewpoint of synthetic stability and handling.

[0095] Furthermore, from the viewpoint of controlling the molecular weight, it is preferred to use a radical polymerization initiator (hereinafter referred to as "polymerization initiator"). Furthermore, known additives such as a chain transfer agent may be used.

[0096] Although not limited to the following examples, examples of the solvent include acetone, methyl ethyl ketone, cyclohexanone, methyl acetate, ethyl acetate, propyl acetate, toluene, xylene, anisole, isopropyl alcohol, propylene glycol monomethyl ether, propylene glycol monoethyl ether, etc. These solvents may be used alone or in combination of two or more.

[0097] In this case, although the solid component content of the acrylic polymer (B) does not impair the synthesis stability and can be arbitrarily selected, the solid component content is usually 10 to 70 mass-%.

[0098] [Polymerization initiator]

[0099] In the present invention, examples of the polymerization initiator that can be used for the acrylic polymer (B) include organic peroxides such as benzoyl peroxide, tert-butyl perbenzoate, cumene hydroperoxide or diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di-(2-ethoxyethyl) peroxydicarbonate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, (3,5,5-trimethylhexanoyl) peroxide, dipropionyl peroxide and diacetyl peroxide; azo compounds, Such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), dimethyl-2,2'-azobis(2-methylpropionate), 4,4'-azobis(4-cyanovaleric acid), 2,2'-cyanobis(2-hydroxymethylpropionitrile) and 2,2'-azobis[2-(2-imidazolin-2-yl)propane]. These polymerization initiators can be used alone or in combination of two or more. The amount of the polymerization initiator added is preferably 0.1 to 20 parts by mass based on 100 parts by mass of the total amount of the hydroxyl-containing monomer (a), the carboxyl-containing monomer (b) and the other monomers (c).

[0100] [Chain transfer agent]

[0101] In the production of the acrylic polymer (B), a chain transfer agent may be used for the purpose of controlling the molecular weight. Examples of the chain transfer agent include thioglycerol, alkyl mercaptans such as octyl mercaptan, nonyl mercaptan, decyl mercaptan and dodecyl mercaptan; thioglycolates such as octyl thioglycolate, nonyl thioglycolate and 2-ethylhexyl thioglycolate; and 2,4-diphenyl-4-methyl-1-pentene, 1-methyl-4-isopropylidene-1-cyclohexane, α-pinene, β-pinene and the like.

[0102] When producing the acrylic polymer (B), the method for adding the solvent and the polymerization initiator is arbitrary, however, in order to control the polymerization heat and the reaction heat, a preferred method is to charge the organic solvent solution into the reaction tank, and while providing stirring, add the radical polymerizable monomer or the organic solvent solution dropwise from the dropping tank. The polymerization temperature of the above-mentioned polymerization reaction varies depending on the type of the polymerization initiator and whether a chain transfer agent is used at the same time, however, it is preferred to carry out the reaction under the condition of 50°C to 200°C, and more preferably, it is carried out under the condition of 80°C to 160°C. Since the 10-hour half-life temperature of many polymerization initiators is 50°C or higher, the desired free radical-induced decomposition efficiency can be obtained by using a polymerization temperature of 50°C or higher. On the other hand, making the polymerization temperature 200°C or lower can reduce side reactions (such as unexpected polymerization).

[0103] [Mass average molecular weight (Mw) of acrylic polymer (B)]

[0104] In the present invention, the mass average molecular weight (Mw) of the acrylic polymer (B) is preferably 1,000 to 50,000, more preferably 2,000 to 40,000 and particularly preferably 3,000 to 30,000. By making the mass average molecular weight 1,000 or higher, chemical resistance obtained by making the topcoat layer (A) have sufficient pencil hardness is ensured. In the case where the mass average molecular weight is 50,000 or lower, the topcoat layer (A) will have good curing agent compatibility, and thus the coating film will have a good appearance.

[0105] In the present invention, the mass average molecular weight (Mw) is measured using gel permeation chromatography (HLC-8220, trade name, Tosoh Corporation). A calibration curve is prepared from a standard polystyrene sample. The eluent used is tetrahydrofuran, and the combination is used. G2000HXL, G3000HXL, G4000HXL and G5000HXL (trade names, Tosoh Corporation) columns were used for the measurement under the conditions of a flow rate of 1.0 mL / min, an injection volume of 10 μL and a column temperature of 40°C.

[0106] [Hydroxy value of acrylic polymer (B)]

[0107] In the present invention, the hydroxyl value of acrylic polymer (B) is 80 to 220mg KOH / g, preferably 100 to 210mg KOH / g and particularly preferably 120 to 200mg KOH / g. When hydroxyl value is 80mg KOH / g or larger, topcoat layer (A) obtains enough pencil hardnesses, and guarantees chemical resistance. When hydroxyl value is 220mg KOH / g or lower, topcoat layer (A) can obtain the total elongation in the target range and has good moldability. In addition, obtained curing agent compatibility, thereby for topcoat layer (A) provides good outward appearance. At this, hydroxyl value is the hydroxyl value measured according to JIS-K1557.

[0108] [Acid value of acrylic polymer (B)]

[0109] In the present invention, the acid value of the acrylic polymer (B) is 0 to 60 mg KOH / g, preferably 0 to 50 mg KOH / g and particularly preferably 0 to 40 mg KOH / g. By making the acid value of the acrylic polymer (B) within the above range, the topcoat layer (A) can have good water resistance. Here, the acid value is the acid value measured according to JIS-K5601.

[0110] [Polyisocyanate (C)]

[0111] In the present invention, a cured film for the topcoat layer (A) having excellent coating film strength and flexibility is obtained through the cross-linking reaction of the acrylic polymer (B) and the polyisocyanate (C).

[0112] From the viewpoint of weather resistance (light resistance, particularly non-yellowing), the polyisocyanate (C) is preferably an aliphatic polyisocyanate compound.

[0113] Furthermore, from the viewpoint of water resistance and chemical resistance, the polyisocyanate (C) is preferably one or more substances selected from the group consisting of biuret, isocyanurate, adduct, uretdione and allophanate compounds having two or more isocyanate groups in the molecule.

[0114] Specific examples of the polyisocyanate (C) are listed below.

[0115] Examples of commercially available polyisocyanate (C) mainly containing biuret include Desmodur N75 (trade name, Sumika Covestro Urethane Co., Ltd.), DURANATE 24A-100 and 22A-75P (trade names, Asahi Kasei Corporation), and the like.

[0116] Examples of commercially available polyisocyanates (C) mainly containing isocyanurate include Desmodur N 3600 and N3300 (trade names, Sumika Covestro Polyurethanes AG), DURANATE TPA-100 and TKA-100 (trade names, Asahi Kasei Corporation), and the like.

[0117] Examples of commercially available polyisocyanate (C) mainly containing an adduct include DURANATE E402-80B and E405-70B (trade names, Asahi Kasei Corporation) and the like.

[0118] Examples of commercially available polyisocyanates (C) mainly containing uretdione include Desmodur N3400 (trade name, Sumika Covestro Polyurethanes AG), and DURANATE TLA-100 and TUL-100 (trade names, Asahi Kasei Corporation).

[0119] Examples of commercially available polyisocyanates (C) mainly containing allophanate include DURANATE A201H, D101, and D201 (trade names, Asahi Kasei Corporation), CORONATE 2793 and 2770 (trade names, Tosoh Corporation), and the like.

[0120] These polyisocyanates (C) may be used alone or in combination of two or more.

[0121] A material in which the isocyanate group has a block (blocked isocyanate) or a material without a block can be used for the polyisocyanate (C). However, from the viewpoint of the low temperature curability of the topcoat layer (A), it is preferred to use a polyisocyanate (C) without a block. That is, if the isocyanate group of the polyisocyanate (C) is blocked, it is necessary to heat to a relatively high temperature (e.g., a temperature higher than 120° C.), and due to this, it is preferred to use an unblocked isocyanate (C) so that deformation does not occur during the curing process of the topcoat layer (A).

[0122] [NCO / OH molar ratio]

[0123] In the present invention, the content ratio of the isocyanate group in the polyisocyanate (C) to the hydroxyl group in the acrylic polymer (B) expressed as the NCO / OH molar ratio is preferably 0.5 to 1.7 and more preferably 0.8 to 1.3. When the NCO / OH molar ratio is 0.5 or more, sufficient crosslinking density can be obtained, the pencil hardness and total elongation of the topcoat layer (A) can reach the target range, and the chemical resistance and moldability are satisfactory. When the NCO / OH molar ratio is 1.7 or less, a coating film having excellent weather resistance is obtained.

[0124] [catalyst]

[0125] In the present invention, coating material (D) can include catalyst to promote the cross-linking reaction of acrylic polymer (B) and polyisocyanate (C). Known metal-based catalysts and amine-based catalysts can be used as catalysts. Metal-based catalysts include dibutyltin dilaurate, tin octoate, di(2-ethylhexanoic acid) dibutyltin, 2-ethylhexanoic acid lead, 2-ethylhexanoic acid titanium, diisopropoxybis(acetylacetone) titanium, 2-ethylhexanoic acid iron, 2-ethylhexanoic acid cobalt, zinc naphthenate, cobalt naphthenate, tetra-n-butyltin etc. Amine-based catalysts include tertiary amines such as tetramethylbutylene diamine. The blending amount of these catalysts is preferably 0.001 to 1 mass part based on 100 mass parts of coating material (D).

[0126] [Solvent]

[0127] In the present invention, the coating material (D) contains a solvent as an essential component. Examples of solvents include alicyclic hydrocarbon-based solvents such as cyclohexane and ethylcyclohexane; aromatic hydrocarbon-based solvents such as toluene, xylene, ethylbenzene and aromatic naphtha; ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone and isophorone; ester-based solvents such as ethyl acetate, n-butyl acetate, isopropyl acetate, 3-methoxybutyl acetate and bis(2-ethylhexyl) adipate; ether-based solvents such as dibutyl ether, tetrahydrofuran, 1,4-dioxane and 1,3,5-trioxane; and nitrogen-based solvents such as acetonitrile, valeronitrile, N,N-dimethylformamide and N,N-diethylformamide, etc. The organic solvent may be a single solvent substance, or may be a multi-substance solvent mixture of two or more solvent substances. The solvent is not particularly limited, provided that it can adjust the viscosity of the coating material (D), can be coated and form the topcoat layer (A), and additionally does not erode the base material. Furthermore, the boiling point of the solvent is preferably below 250°C.

[0128] The solvent content in 100 parts by mass of the coating material (D) of the present invention is preferably 10 to 90 parts by mass. Making the solvent content 10 parts by mass or more enables the wettability to the base material to be controlled, and making the solvent content 90 parts by mass or less enables the film thickness of the topcoat layer (A) to be adjusted.

[0129] In the present invention, the coating material (D) may comprise one or more substances selected from polyurethane elastomers (E) or polyesters (F). Adding one or more substances selected from polyurethane elastomers (E) or polyesters (F) to the coating material (D) can further improve the total elongation of the topcoat layer (A) due to plasticization, and can accordingly adapt to more complex shapes.

[0130] [Polyurethane elastomer (E)]

[0131] The content of the polyurethane elastomer (E) in 100 parts by mass of the coating material (D) is preferably 1 to 50 parts by mass, more preferably 3 to 40 parts by mass, and still more preferably 5 to 30 parts by mass. When the content of the polyurethane elastomer (E) is 1 to 50 parts by mass, excellent moldability, chemical resistance, and water resistance can be obtained.

[0132] Commercial products of the polyurethane elastomer (E) include Elastollan ET890, CD64-D, and C85A (trade names, BASF), etc. These polyurethane elastomers (E) may be used alone, or two or more kinds may be used.

[0133] [Polyester (F)]

[0134] In the present invention, the coating material (D) may contain polyester (F). The polyester (F) preferably contains hydroxyl groups. The chemical resistance and water resistance of the topcoat layer (A) are improved by the crosslinking reaction of the hydroxyl groups of the polyester (F) and the polyisocyanate (C).

[0135] The content of the polyester (F) in 100 parts by mass of the coating material (D) is preferably 3 to 50 parts by mass, more preferably 6 to 40 parts by mass, and still more preferably 10 to 30 parts by mass. When the content of the polyester (F) is 3 to 50 parts by mass, excellent moldability, chemical resistance, and water resistance can be obtained.

[0136] Polyester (F) can be produced by a common method, for example, by esterification reaction of a polyacid and a polyol. A polyacid is a compound having two or more carboxyl groups in a single molecule, and examples include phthalic acid, isophthalic acid, terephthalic acid, succinic acid, adipic acid, azelaic acid, sebacic acid, tetrahydrophthalic acid, hexahydrophthalic acid, maleic acid, fumaric acid, itaconic acid, trimellitic acid, pyromellitic acid and anhydrides thereof, and the like. The polyol is a compound having two or more hydroxyl groups in a single molecule, and examples include diols such as ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 2,2-diethyl-1,3-propanediol, neopentyl glycol, 1,9-nonanediol, 1,4-cyclohexanediol, hydroxypivalic acid neopentyl glycol ester, 2-butyl-2-ethyl-1,3-propanediol, 3-methyl-1,5-pentanediol, 2,2,4-trimethylpentanediol and hydrogenated bisphenol A; and polyol components having a valence of three or more such as trimethylolpropane, trimethylolethane, glycerol and pentaerythritol; and hydroxycarboxylic acids such as 2,2-dimethylolpropionic acid, 2,2-dimethylolbutanoic acid, 2,2-dimethylolpentanoic acid, 2,2-dimethylolhexanoic acid and 2,2-dimethyloloctanoic acid and the like.

[0137] Commercial products of the polyester (F) include D620, D623, D643, and D645 (trade names, Mitsubishi Chemical Corporation), ADK CYCLOAID PNB series (trade name, ADEKA Corporation), and the like.

[0138] In addition, commercial products of the hydroxyl-containing polyester (F) include K-FLEX 188, 171-90, A307, A308, and UD-320-100 (trade names, King Industries, Inc.), Desmophen C 1200 and 3601 (trade names, Covestro), and the like.

[0139] The hydroxy value of the hydroxyl group-containing polyester (F) is preferably in the range of 10 to 300 mg KOH / g, and more preferably in the range of 10 to 250 mg KOH / g.

[0140] The mass average molecular weight (Mw) of the polyester (F) is preferably in the range of 500 to 30,000.

[0141] These polyesters (F) may be used alone, or two or more kinds may be used.

[0142] [Hindered amine-based light stabilizers (G)]

[0143] In the present invention, the coating material (D) may include a hindered amine-based light stabilizer (G) and is preferably used in combination with an ultraviolet absorber (J). As the outermost surface layer on an exterior part on an automobile or other such coated object, the topcoat layer (A) of the present invention may be exposed to all changes in outdoor weather for a long period of time. However, by using an ultraviolet absorber (J) in combination with a hindered amine-based light stabilizer (G) as described above, the coating can be kept close to the conditions at the time of delivery for 10 years or more.

[0144] A particularly preferred example is one in which a triazine-based ultraviolet absorber (J) and a NOR-type hindered amine-based light stabilizer (G) are added to the coating material (D).

[0145] Commercially available triazine-based UV absorbers (J) include, for example 40, Eversorb 41FD and Eversorb 45 (trade names, Everlight Chemical), Tinuvin 1600 and Tinuvin 1577ED (trade names, BASF), etc. These triazine-based ultraviolet absorbers (J) may be used alone, or two or more kinds may be used.

[0146] Commercially available NOR-type hindered amine-based light stabilizers (G) include Eversorb 93, Eversorb 90, and Eversorb 95 (trade names, Everlight Chemical Co., Ltd.), and Tinuvin 123, Tinuvin 144, Tinuvin 765, and Tinuvin 770 (trade names, BASF Corporation), etc. These NOR-type hindered amine-based light stabilizers (G) may be used alone, or two or more may be used.

[0147] The contents of the ultraviolet absorber (J) and the hindered amine-based light stabilizer (G) in 100 parts by mass of the coating material (D) are preferably 0.1 to 30 parts by mass, more preferably 0.1 to 25 parts by mass, and still more preferably 0.1 to 20 parts by mass. When the contents of the ultraviolet absorber (J) and the hindered amine-based light stabilizer (G) are 0.1 to 30 parts by mass, respectively, excellent weather resistance can be obtained.

[0148] [other]

[0149] In the present invention, the coating material (D) can be used as it is, or it can be used with the addition of one or more of various additives, such as antioxidants, surfactants, surface conditioners, antistatic agents, fragrances or dehydrating agents, and additionally rheology modifiers such as polyethylene wax, polyamide wax and internally cross-linked resin fine particles, etc.

[0150] Furthermore, the coating material (D) may be used as a transparent coating material, or it may be blended with a colorant such as a dye or a pigment, and then used as a colored coating material.

[0151] [Production of coating material (D)]

[0152] In the present invention, the coating material (D) can be produced by a known method. As a specific example, an acrylic polymer (B) (which contains a hydroxyl group and has a glass transition temperature of -50°C to 30°C), a polyisocyanate (C) and a solvent are added in order to provide the desired coating material properties. After sufficient mixing, coarse particles are removed by filtration or other means to obtain the coating material (D).

[0153] [Production of topcoat layer (A)]

[0154] In the present invention, the topcoat layer (A) is produced by applying a coating material (D) to a substrate. Although the method for applying the coating material (D) to the substrate is not particularly limited, examples of known methods include rod coating, scraper coating, roller coating, plate coating, die coating, gravure coating, curtain coating, spray coating, etc. Then, baking evaporates the solvent and promotes the crosslinking reaction to obtain the topcoat layer (A).

[0155] [Base material]

[0156] In the present invention, the base material to which the coating material (D) is applied is not particularly limited.

[0157] Specifically, the base material includes one or more resins selected from the group consisting of: (meth) acrylic resin, styrene-based resin, polycarbonate-based resin, polyolefin-based resin, polyvinyl chloride, polyester, polyvinyl acetate, vinyl acetate copolymer, styrene-methyl methacrylate copolymer, acrylonitrile-styrene copolymer, acrylonitrile-butadiene-styrene copolymer, nylon, polymethylpentene, silicone resin, amino resin, polysulfone, polyethersulfone, polyetherimide, fluororesin and polyimide resin material, and in addition, including dust-free paper, glass base material, porous ceramic base material, cellulose base material, etc. The form of the base material is not particularly limited, however, preferably sheet form, plate form, etc. From the perspective of moldability, a base material as a polypropylene film is particularly preferred.

[0158] The thickness of the base material is generally 50 to 1000 μm and preferably about 100 to 1000 μm. If the thickness of the base material is less than 50 μm, the processing capability may be reduced.

[0159] Since the base material film may be subjected to heat load during molding, it is preferred that the base material is heat-resistant. Cracks in the topcoat layer (A) do not tend to form because deformation of the base material is thereby reduced, and because the adhesion state (adhesion) with the topcoat layer (A) laminated adjacently to the base layer can be preferably maintained. With regard to heat resistance in the present invention, if no deformation is observed after the base material is inserted into a 120° C. oven for 5 seconds, substantially no deformation should be observed.

[0160] In addition, these base materials can be pre-treated on the surface in advance, and a coating film can be pre-formed on the surface. That is, in addition to physical treatments (such as corona treatment, flame treatment, and plasma treatment of the base material surface), easy adhesion treatments for laying a primer (such as chlorinated olefins, polyesters, or urethanes) layer can be performed. Performing these treatments improves the bonding strength of the base material to the adjacent layers.

[0161] The thickness of the primer layer material is generally 1 to 100 μm and preferably about 1 to 20 μm. If the thickness of the primer layer is greater than 100 μm, weather resistance may be reduced.

[0162] [Laminating film (H)]

[0163] The laminated film (H) of the present invention can take five forms as presented in the following examples. The description presented refers to the accompanying drawings.

[0164] [Example 1]

[0165] like Figure 1The laminated film (H1) in Example 1 shown in is a laminated film (H1) in which a primer layer 2 and a topcoat layer (A) are sequentially formed on a base material 1. For example, the method for producing the laminated film (H1) in Example 1 includes laying a primer layer 2 on a base material 1, and further, applying a coating material (D) which is previously prepared by diluting a desired arbitrary component mixture of an acrylic polymer (B), a polyisocyanate (C) and a solvent to provide a topcoat layer (A), thereby forming the laminated film (H1).

[0166] [Example 2]

[0167] like Figure 2 The laminated film (H2) in Example 2 shown in is a laminated film (H2) in which a primer layer 2, a print layer 3, and a topcoat layer (A) are sequentially formed on a base material 1. For example, the method for producing a laminated film (H2) in Example 2 includes laying a primer layer 2 and a print layer 3 on a base material 1, and further, applying a coating material (D) to the print layer 3 to provide a topcoat layer (A), thereby forming a laminated film (H2), the coating material being prepared in advance by diluting a desired arbitrary component mixture of an acrylic polymer (B), a polyisocyanate (C), and a solvent.

[0168] [Example 3]

[0169] like Figure 3 The laminated film (H3) in Example 3 of the present invention shown in is a laminated body in which a primer layer 2 and a printed pattern layer 4 are applied to a base material 1, and subsequently, a topcoat layer (A) is additionally laminated. For example, the method for producing the laminated film (H3) in Example 3 includes laying a primer layer 2 and a printed pattern layer 4 on a base material 1, and further, applying a coating material (D) which is prepared in advance by diluting a desired arbitrary component mixture of an acrylic polymer (B), a polyisocyanate (C), and a solvent to provide a topcoat layer (A), thereby forming a laminated film (H3).

[0170] [Example 4]

[0171] like Figure 4 The laminated film (H4) in Example 4 of the present invention shown in is a laminated film (H4) formed by coating the back surface of the base material 1 of the laminated film (H1) or (H2) in Example 1 or Example 2 with an adhesive layer 6, and then covering the topcoat layer (A) and the adhesive layer 6 with a peeling layer 5.

[0172] [Example 5]

[0173] like Figure 5The laminated film (H5) in Example 5 of the present invention shown in is a laminated body in which a release layer 5 is used instead of the base material 1. The laminated film (H5) is formed by coating the top of the release layer 5 with a coating material (D) prepared in advance by diluting a desired arbitrary component mixture of an acrylic polymer (B), a polyisocyanate (C) and a solvent, and further covering the top of the topcoat layer (A) with the release layer 5.

[0174] The details of the printing layer, the printing pattern layer and the release layer used in the above five embodiments are as follows.

[0175] [Printing layer and printed pattern layer]

[0176] The printing layer or the printing pattern layer can be formed by using metal or ink. When using metal, the specified pattern can be formed by using vapor deposition or sputtering patterning process, etc. When using ink, the printing layer or the printing pattern layer can be formed on the base material film by a printing method such as gravure printing, flexographic printing, screen printing or sublimation thermal transfer.

[0177] [Peeling layer]

[0178] There is no particular limitation on the release layer, and a known release film can be used. Examples of substances that can be used as the release layer are films such as polyester, polyvinyl chloride, polyvinylidene chloride, and polyethylene terephthalate that have been subjected to a release treatment by applying a silicone resin, a fluororesin, or the like to the contact surface with the topcoat layer (A), paper such as high-grade paper and glass paper, or a laminated film of high-grade paper or glass paper and polyolefin, and the like. The thickness of the release layer is usually 10 μm to 200 μm and preferably 25 μm to 100 μm.

[0179] The peel strength of the peeling layer and the topcoat layer (A) is preferably 0.05 to 8.0 N / 25 mm and more preferably 0.1 to 5.0 N / 25 mm. When the peel strength is 0.05 N / 25 mm or more, the peeling layer is not separated from the topcoat layer (A) during the production process of the laminated film (H), during the decorative molding process, etc., and moldability is improved. By having a peel strength of 8.0 N / 25 mm or less, when the peeling layer is removed after decorative molding, the peeling layer peels off smoothly.

[0180] The peel strength of the peel layer and the topcoat layer (A) was measured according to the 180° peel bond strength test of adhesives of JIS K6854.

[0181] [Adhesive layer]

[0182] The adhesive layer may be applied to the back surface of the base material. The resin component used in the adhesive layer is not particularly limited as long as it can adhere to the base material and the decorative article, and polyurethane resins, polyester resins, polyvinyl acetate resins, epoxy resins, etc. may be used. These resin components may be used alone, or a mixture of a plurality of resin components may be used.

[0183] [Total elongation of laminated film (H)]

[0184] In the present invention, "a total elongation of 5% or more in a temperature range of 60°C to 120°C" of the laminated film (H) indicates a total elongation of 5% or more at any temperature in the temperature range of 60°C to 120°C and means that sufficient stretchability is obtained when formed at this temperature. When the total elongation is 5% or more in a temperature range of 60°C to 120°C, no breakage will occur in its topcoat layer (A) when the laminated film (H) is stretched, and a good appearance of the molded article is maintained. In order to measure the total elongation, a sample of the laminated film (H) having a size of initial length (L0) = 30 mm and width = 10 mm is prepared, and measured at a stretching speed of 5 mm / min in a temperature range of 60°C to 120°C using Autoclave AG-IS (trade name) manufactured by Shimadzu Corporation. The length (L) at the breaking point of any layer is measured, and the total elongation is determined by the following formula.

[0185] Total elongation (%) = (L-L0) / L0 x 100

[0186] [Decorative products (I)]

[0187] In the present invention, the decorative article (I) is not particularly limited, and examples of the present invention of the article to be decorated by using the laminate film (H) on the object to be decorated include vehicle parts such as automobile bodies, emblems, and vehicle exteriors and interiors; building material parts such as wall finishing materials, window glass, window frames, and bathroom wall finishing materials; daily products such as tableware, toys, and musical instruments; home appliance parts such as vacuum cleaner housings, TV housings, and air conditioner housings; interior parts such as doors; transportation parts, etc. Among these, the decorative article (I) of the present invention can be suitably used for improving both the design and durability of automobile plastic parts due to excellent chemical resistance, water resistance, and weather resistance based on the characteristics of the laminate film (H).

[0188] Example

[0189] The present invention is further described in detail below based on examples, however, the scope of rights of the present invention should not be construed as being limited by the following examples. In the examples, unless otherwise specified, "parts" means "parts by mass", and "%" related to blending amount and content means "mass %". In addition, Mw represents mass average molecular weight, and Tg represents glass transition temperature.

[0190] <Synthesis of Acrylic Polymer (B)>

[0191] [Synthesis Example 1]

[0192] While introducing nitrogen, 100 parts of MEK solvent are added to a four-necked flask equipped with a reflux condenser tube, a dropping funnel, a gas introduction tube, a stirring device and a thermometer, and heated and stirred at 75°C for 30 minutes. A mixture of 2.0 parts of monomer ST, 20.0 parts of BA, 45.0 parts of EHA, 15.0 parts of HEA, 17.0 parts of HPMA and 1.0 parts of AA and 1.0 parts of polymerization initiator AIBN is placed in a dropping funnel, and the mixture is added dropwise for 3 hours while maintaining an internal temperature of 75°C. Stirring is maintained for another 5 hours. After confirming that the addition rate exceeds 98% by measuring the solid content, cooling is applied, and MEK is completely evaporated by a vacuum pump to obtain an acrylic polymer (B-1).

[0193] [Synthesis Examples 2 to 12]

[0194] Except for the changes in the composition and the blending ratio in Table 1, the acrylic polymers (B-2) to (B-12) were obtained by the same production method as that of the acrylic polymer (B-1).

[0195] [Table 1]

[0196] Table 1 - Production of acrylic polymer (B)

[0197]

[0198] The value of each material indicates parts by mass.

[0199] The meanings of the abbreviations in Table 1 are presented below.

[0200] <Monomer (a)>:

[0201] HEA: 2-Hydroxyethyl Acrylate

[0202] HEMA: 2-Hydroxyethyl Methacrylate

[0203] HPMA: 2-Hydroxypropyl Methacrylate

[0204] <Monomer (b)>:

[0205] AA: Acrylic acid

[0206] <Monomer (c)>:

[0207] ST: Styrene

[0208] BMA: Butyl Methacrylate

[0209] BA: Butyl acrylate

[0210] EHA: 2-Ethylhexyl Acrylate

[0211] MMA: Methyl Methacrylate

[0212] <Solvent>

[0213] MEK: Methyl Ethyl Ketone

[0214] <Polymerization Initiator>

[0215] AIBN: 2,2-azobis(isobutyronitrile)

[0216] [Application Example 1]

[0217] [Preparation of coating material (D-1)]

[0218] 46.2 parts of acrylic polymer (B-1), 20.9 parts of polyisocyanate (C-4), 1 part of triazine-based ultraviolet absorber (J-1), 1 part of hindered amine-based light stabilizer (G-1) and 0.01 part of catalyst (dibutyltin dilaurate) were weighed and diluted with a solvent (ethyl 3-ethoxypropionate (EEP)) to a solid content (referred to as "coating NV") of 49 mass-%, and stirred in an oscillator until sufficiently uniform. Subsequently, it was filtered with a membrane filter having a mesh opening of 200 μm to remove coarse particles and prepare a coating material (D-1). The above materials are described in Table 2.

[0219] [Application Examples 2 to 19], [Comparative Examples 1 to 6]

[0220] [Preparation of coating materials (D-2) to (D-25)]

[0221] Coating materials (D-2) to (D-25) were prepared using the same method as Application Example 1 by changing the blending ratio as shown in Table 2.

[0222] [Table 2]

[0223]

[0224] The meanings of the abbreviations in Table 2 are presented below.

[0225] Polyisocyanate (C-1): DURANATE 24A-100 (trade name) manufactured by Asahi Kasei Corporation (mainly containing biuret)

[0226] Polyisocyanate (C-2): DURANATE E402-80B (trade name) manufactured by Asahi Kasei Corporation (mainly containing an adduct)

[0227] Polyisocyanate (C-3): DURANATE A201H (trade name) manufactured by Asahi Kasei Corporation (mainly containing allophanate)

[0228] Polyisocyanate (C-4): DURANATE TPA-100 (trade name) manufactured by Asahi Kasei Corporation (mainly containing isocyanurate)

[0229] Polyurethane elastomer (E-1): Elastollan ET 890 (trade name) manufactured by BASF

[0230] Polyester (F-1): K-FLEX 188 (trade name) manufactured by King Industries

[0231] Polyester (F-2): Desmophen C1200 (trade name) manufactured by Covestro

[0232] Triazine-based UV absorber (J-1): Eversorb 40 (trade name) manufactured by Everlight Chemical Co., Ltd.

[0233] Hindered amine-based light stabilizer (G-1): Eversorb 93 (trade name) manufactured by Everlight Chemical Co., Ltd.

[0234] [Measurement of Viscosity of Coating Materials (D-1) to (D-25)]

[0235] 1 ml of each coating material (D-1) to (D-25) was placed in a TVE 25L ​​viscometer (trade name) manufactured by Toki Sangyo Co., Ltd, and the viscosity was measured at 23° C. and 50 rpm. The evaluation results are presented in Table 2 with the following indices.

[0236] ◎: 50 mPa·s ≤ coating material viscosity ≤ 5000 mPa·s, can be easily coated, and a sufficient film thickness can be obtained.

[0237] ×: The coating material viscosity is <50 mPa·s or the coating material viscosity is >5000 mPa·s, and a sufficient film thickness cannot be obtained, or coating is difficult.

[0238] [Preparation of topcoat layer (A-1) and laminated film (H5-1)]

[0239] The top of a release film GS (trade name) manufactured by Lintec Corporation was coated with a coating material (D-1) using a coater to achieve a dry film thickness of 30 μm. Next, the release film GS was pasted onto the coating film surface before drying so as to be closely pasted. The thus obtained three-layer structure film (in which the coating film layer was formed between the release layers) was heat-dried in an oven at 80° C. for 4 days to obtain a laminated film (H5-1). Subsequently, the release layer was removed to obtain a liner-free film (single-layer film) of the topcoat layer (A-1).

[0240] [Preparation of topcoat layers (A-2) to (A-25) and laminated films (H5-2) to (H5-25)]

[0241] The laminated films (H5-2) to (H5-25) described in Table 3 were obtained by using the coating materials (D-2) to (D-25) obtained by the same method as the laminate (H5-1). Subsequently, the peeling layer was removed to obtain the unlined film of the topcoat layer (A-2) to (A-25). From the unlined film of these topcoat layers (A-1) to (A-25), the evaluation samples were taken out and tested as described below.

[0242] [Table 3]

[0243] Table 3 - Topcoat layer (A) composition and physical properties

[0244]

[0245] [Application Example 20]

[0246] [Preparation of Laminated Film (H1-1)]

[0247] On a horizontal platform, primer (K-1) was applied to the surface of a 200 μm thick corona-treated unstretched polypropylene film with a coater to a dry film thickness of 5 μm. After standing at room temperature for 5 minutes, coating material (D-1) was applied with a coater to a dry film thickness of 30 μm to form a topcoat layer (A-1). Subsequently, it was heat-dried in an oven at 80° C. for 4 days to obtain a laminated film (H1-1).

[0248] [Application Examples 21 to 29, 33 to 38], [Comparative Examples 7 to 12]

[0249] [Preparation of Laminated Films (H1-2 to 10, H1-14 to 25)]

[0250] The laminated films (H1-2 to 10, H1-14 to 25) described in Table 4 were obtained by the same method as the laminate (H1-1) using the coating materials (D2 to 10, 14 to 25). Evaluation samples were taken out from these laminated films, and tested as described below.

[0251] [Table 4]

[0252] Table 4 - Laminated Film (H) Composition and Physical Properties

[0253]

[0254] The meanings of the abbreviations in Table 4 are as follows.

[0255] Primer (K-1): SUPERCHLON 930 (trade name) manufactured by Nippon Paper Industries Co., Ltd.

[0256] [Application Example 30]

[0257] [Preparation of Laminated Film (H2-1)]

[0258] On a horizontal platform, the primer (K-1) was applied to the surface of a 200 μm thick corona-treated unstretched polypropylene film with an applicator to a dry film thickness of 5 μm. After standing at room temperature for 5 minutes, a continuous layer with a dry film thickness of 1 μm was gravure-printed using ink A to obtain a printed layer (L-1).

[0259] After standing at room temperature for 5 minutes, the coating material (D-11) was applied to a dry film thickness of 30 μm with an applicator to form a topcoat layer (A-11). Subsequently, it was heat dried in an oven at 80° C. for 4 days to obtain a laminated film (H2-1). The details of the laminated film (H2-1) are described in Table 4.

[0260] Note that the above-mentioned ink A is produced in advance by the following method.

[0261] <Production of Ink A>

[0262] 10 parts of yellow pigment (CI Pigment Yellow 83: LIONOL YELLOW 1805G, manufactured by Toyocolor Co., Ltd.), 40 parts of polyurethane resin PU1 solution, 15 parts of vinyl chloride copolymer resin (Solbin TAR5 manufactured by Nissin Chemical Industry Co., Ltd.: vinyl acetate: vinyl alcohol = 88:1:11 (solid content 25% ethyl acetate solution)), 25 parts of ethyl acetate and 10 parts of isopropyl alcohol (IPA) were mixed and stirred in a disperser. Subsequently, it was dispersed for 10 minutes using a sand mill to obtain ink A.

[0263] Furthermore, the above-mentioned polyurethane PU1 was synthesized according to the following description.

[0264] <Synthesis of polyurethane resin PU1>

[0265] 100 parts of a polyester polyol having a number average molecular weight of 5,000 (which is a condensate of 3-methyl-1,5-pentanediol and adipic acid), 24 parts of a polyester polyol having a number average molecular weight of 2,000 (which is a condensate of propylene glycol and adipic acid), 16 parts of a polypropylene glycol having a number average molecular weight of 2,000, 20.5 parts of isophorone diisocyanate and 73.7 parts of ethyl acetate were reacted at 80° C. under a nitrogen stream for 4 hours to obtain a solvent solution of a terminal isocyanate urethane prepolymer. Next, the obtained terminal isocyanate urethane prepolymer solution was gradually added to a mixture of 8.2 parts of isophoronediamine, 0.5 parts of 2-ethanolamine, 222.9 parts of ethyl acetate and 127.1 parts of isopropanol at 40° C., and then reacted at 80° C. for 1 hour to obtain a polyurethane resin PU1 solution having a solid content of 30%, an amine value of 3.5 mg KOH / g, a hydroxyl value of 1.7 mg KOH / g, a mass average molecular weight of 50,000 and a glass transition temperature of −40° C.

[0266] [Application Example 31]

[0267] [Preparation of Laminated Film (H3-1)]

[0268] On a horizontal platform, primer (K-1) was applied to the surface of a 200 μm thick corona treated unstretched polypropylene film with an applicator to a dry film thickness of 5 μm. After standing at room temperature for 5 minutes, the pattern layer with a dry film thickness of 1 μm was gravure printed using the above-mentioned ink A to obtain a printed pattern layer (L-2). After standing at room temperature for 5 minutes, a coating material (D-12) was applied to a dry film thickness of 30 μm to form a topcoat layer (A-12). Subsequently, it was heat dried in an oven at 80 ° C for 4 days to obtain a laminated film (H3-1). The details of the laminated film (H3-1) are described in Table 4.

[0269] [Application Example 32]

[0270] [Preparation of Laminated Film (H4-1)]

[0271] On a horizontal platform, primer (K-1) was applied to the surface of a 200 μm thick corona treated unstretched polypropylene film with a coating device to a dry film thickness of 5 μm. After standing for 5 minutes at room temperature, a coating material (D-13) was applied to a dry film thickness of 30 μm to form a topcoat layer (A-13) with a coating device. Next, before drying, a peeling film GS (trade name) manufactured by Lindec Co., Ltd. was pasted on the top surface of the coating film to firmly paste. The four-layer structural film including a base material, a primer layer, a topcoat layer (A-13) and a peeling layer thus obtained was heat dried in an oven at 80 ° C for 4 days. Subsequently, SK Dyne 1310DT (trade name) manufactured by Soken Chemical & Engineering Co., Ltd. was applied to the opposite surface of the base material with a coating device to a dry film thickness of 100 μm, to form an adhesive layer. Then, a release film GS was laminated onto the adhesive layer to obtain a laminated film (H4-1). The details of the laminated film (H4-1) are described in Table 4.

[0272] Evaluation tests of the topcoat layer (A) and the laminated film (H) produced as described above were carried out in the manner described below.

[0273] [evaluate]

[0274] [Total elongation of topcoat layer (A)]

[0275] A non-liner film of the topcoat layer (A) having dimensions of initial length (L0) = 30 mm, width = 10 mm and film thickness 30 μm was prepared, and the total elongation was measured at a tensile speed of 5 mm / min at temperatures of 23° C., 60° C. and 100° C. using Autoclave AG-IS (trade name) manufactured by Shimadzu Corporation. The length (L) at the rupture point of the topcoat layer (A) was measured, and the total elongation was determined by the following formula.

[0276] Total elongation (%) = (L-L0) / L0 x 100

[0277] The evaluation results are presented in Table 3 using the following indicators.

[0278] ◎: Total elongation is 20% or more.

[0279] ○: The total elongation is 6% or more and less than 20%.

[0280] △: The total elongation is 3% or more and less than 6%.

[0281] ×: The total elongation is less than 3%.

[0282] [Total elongation of laminated film (H)]

[0283] A sample of the laminated film (H) having a size of initial length (L0) = 30 mm and width = 10 mm was prepared, and the total elongation was measured using Autoclave AG-IS (trade name) manufactured by Shimadzu Corporation at a temperature of 60° C. and 100° C. at a tensile speed of 5 mm / min. The length (L) at the breaking point of any layer was measured, and the total elongation was determined by the following formula.

[0284] Total elongation (%) = (L-L0) / L0 x 100

[0285] The evaluation results are presented in Table 4 using the following indicators.

[0286] ◎: Total elongation is 40% or more.

[0287] ○: The total elongation is 10% or more and less than 40%.

[0288] △: The total elongation is 5% or more and less than 10%.

[0289] ×: The total elongation is less than 5%.

[0290] [Pencil hardness of topcoat layer (A)]

[0291] In the present invention, the pencil hardness of the topcoat layer (A) is measured according to ISO 15184.

[0292] The evaluation results are presented in Table 3 using the following indicators.

[0293] ◎: 2B or higher.

[0294] ○: 4B or higher, 3B or lower.

[0295] △: 6B or higher, 5B or lower.

[0296] ×: 7B or less.

[0297] [Moldability]

[0298] [Topcoat layers (A-1) to (A-25)]

[0299] The unlined films of the topcoat layers (A-1) to (A-25) of the application examples and comparative examples were cut into A4 size. The unlined film was placed on a metal mold of 20 mm length × 30 mm width × 5 mm thickness having a curved surface portion R5, and molded at heating temperatures of 23° C., 60° C., and 100° C. using a vacuum molding machine. That is, the metal mold was used as a pressing substrate having a curved surface portion, and the pressing substrate was pressed in a state covering almost the entire surface of the unlined film. Subsequently, a magnifying glass was used to observe the fractures in the unlined film molded topcoat layers (A-1 to 25).

[0300] The evaluation results are presented in Table 3 using the following indicators.

[0301] ◎: Absolutely no fracture was observed.

[0302] ○: Some breakage.

[0303] △: Moderate amount of breakage.

[0304] ×: Many breaks.

[0305] [Laminated films (H1-1) to (H1-10), (H1-14) to (H1-25), (H2-1), (H3-1), (H4-1)]

[0306] The topcoat layer laminated films (H1-1) to (H1-10), (H1-14) to (H1-25), (H2-1), (H3-1) and (H4-1) of the application examples and comparative examples were cut into A4 size. The laminated film was placed on a metal mold of 20 mm length × 30 mm width × 5 mm thickness having a curved surface portion R5, and molded with a vacuum molding machine at heating temperatures of 60°C and 100°C. That is, the metal mold was used as a pressing substrate having a curved surface portion, and the pressing substrate was pressed in a state covering almost the entire surface of the laminated film. Subsequently, a magnifying glass was used to observe the fractures in the laminated film molded topcoat layers (H1-1) to (H1-10), (H1-14) to (H1-25), (H2-1), (H3-1) and (H4-1). It should be noted that for the laminated film H4-1, the test was performed after removing the peeling layers on both sides.

[0307] The evaluation results are presented in Table 4 using the following indicators.

[0308] ◎: Absolutely no fracture was observed.

[0309] ○: Some breakage.

[0310] △: Moderate amount of breakage.

[0311] ×: Many breaks.

[0312] [Weather resistance]

[0313] [Topcoat layers (A1) to (A-25)], [laminated films (H1-1) to (H1-10), (H1-14) to (H1-25), (H2-1), (H3-1) and (H4-1)] were each subjected to 3000 hours of exposure using a sunlight carbon arc lamp type accelerated weathering tester (JIS K-5400 (1990) 9.8.1), and then, the sample conditions were visually evaluated. Note that, with respect to the unlined film of the topcoat layer (A) and the laminated film (H4-1), the test was performed after removing the release layers on both sides.

[0314] The evaluation results are presented in Tables 3 and 4 using the following indicators.

[0315] ◎: Almost no change was seen.

[0316] ○: Slight whitening or separation of the base material was observed.

[0317] △: Whitening or base material separation is observed, but still usable.

[0318] ×: Clear whitening or base material separation was observed, and it was not usable.

[0319] [Chemical resistance]

[0320] [Topcoat layers (A-1) to (A-25)], laminated films (H1-1) to (H1-10), (H1-14) to (H1-25), (H2-1), (H3-1), (H4-1)]

[0321] A drop of 0.2 ml of a 40% sulfuric acid aqueous solution was placed on the sample and heated to 60°C for 15 minutes. Subsequently, the sample was rinsed with water, and the degree of staining was visually observed. Note that, regarding the unlined film of the topcoat layer (A) and the laminated film (H4-1), the test was performed after removing the peeling layers on both sides.

[0322] The evaluation results are presented in Tables 3 and 4 using the following indicators.

[0323] ◎: Almost no change was seen.

[0324] ○: Slight water stains were seen.

[0325] △: Water stains are visible, but usable.

[0326] ×: Visible water stains are visible and unusable.

[0327] [Water resistance]

[0328] Samples of [topcoat layers (A-1) to (A-25)], laminated films (H1-1) to (H1-10), (H1-14) to (H1-25), (H2-1), (H3-1), and (H4-1)] were immersed in 40° C. warm water for 240 hours, and then, the appearance (wrinkling, cracking) was visually observed. Note that, regarding the unlined film of the topcoat layer (A) and the laminated film (H4-1), the test was performed after removing the release layers on both sides.

[0329] The evaluation results are presented in Tables 3 and 4 using the following indicators.

[0330] ◎: Almost no change was seen.

[0331] ○: Slight amounts of wrinkling and cracking were observed.

[0332] △: Wrinkling and cracking are seen, but it is usable.

[0333] ×: Significant wrinkling and cracking were observed, and it was unusable.

[0334] The present invention made by the inventors has been specifically described based on the above embodiments, however, it goes without saying that the present invention is not limited to the above embodiments and various changes can be made within the scope not departing from the essential contents of the present invention.

[0335] Industrial Applicability

[0336] The topcoat layer (A) of the present invention has good moldability, and the decorative part (I) which has been decorated by the laminated film (H) (in which the topcoat layer (A) has been additionally laminated on the surface of an arbitrary base material) has excellent appearance, chemical resistance, water resistance and weather resistance, and due to this, is suitable for, for example, automobile bodies, bumpers, both interior and exterior automobile parts, building material parts, daily products, household appliance parts, interior parts, ship parts, etc., and can be particularly suitable for automobile plastic parts.

[0337] Description of Reference Numerals

[0338] 1. Base material

[0339] 2 Primer layer

[0340] (A) Topcoat layer (A)

[0341] 3 Printing layer

[0342] 4 Printing pattern layer

[0343] 5 Peeling layer

[0344] 6 Adhesive layer

Claims

1. A topcoat layer (A) which satisfies the following conditions (1) to (3): is formed by applying a coating of a coating material (D) comprising the following essential components: an acrylic polymer (B) comprising a hydroxyl group and having a glass transition temperature of -50°C to 30°C, a polyisocyanate (C), and a solvent; Having a total elongation of 3% or more in the temperature range of 20°C to 120°C; Having a pencil hardness of 6B or higher as measured in accordance with ISO 15184.

2. The topcoat layer (A) according to claim 1, wherein The hydroxyl value of the acrylic polymer (B) is 80 to 220 mg KOH / g.

3. The topcoat layer (A) according to claim 1 or claim 2, wherein The polyisocyanate (C) is an aliphatic polyisocyanate.

4. The topcoat layer (A) according to claim 1 or claim 2, wherein The polyisocyanate (C) is one or more substances selected from the group consisting of biuret, isocyanurate, adduct, uretdione and allophanate of a compound having two or more isocyanate groups in the molecule.

5. The topcoat layer (A) according to claim 1 or claim 2, wherein The coating material (D) further comprises one or more substances selected from polyurethane elastomers (E) or polyesters (F).

6. The topcoat layer (A) according to claim 1 or claim 2, wherein The content ratio of the isocyanate groups in the polyisocyanate (C) to the hydroxyl groups in the above acrylic polymer (B) expressed as a NCO / OH molar ratio is 0.5 to 1.

7.

7. The topcoat layer (A) according to claim 1 or claim 2, wherein The coating material (D) further comprises a hindered amine-based light stabilizer (G).

8. A laminated film (H) in which the topcoat layer (A) according to claim 1 or claim 2 is laminated onto a base material.

9. The laminated film (H) according to claim 8, which has a printed layer between the base material and the topcoat layer (A).

10. The laminated film (H) according to claim 8, wherein The total elongation is 5% or more in the temperature range of 60°C to 120°C.

11. The laminated film (H) according to claim 8, wherein The base material is polypropylene.

12. The laminated film (H) according to claim 8, wherein The release layer is further laminated onto the topcoat layer (A).

13. A decorative article (I) decorated with the laminated film (H) according to claim 8.

Citation Information

Patent Citations

  • Conductive composition of molding film, molding film and its manufacturing method, compact and its manufacturing method

    JP2021017507A

  • Decorative film

    WO2018216741A1